Implementation of the Motor Vehicle Tax Elimination Program in the Perspective of Public Service Transformation in the Revenue Technical Implementation Unit of Region V of Banggai Regency - Rian Agustian; Nawawi Natsir; Sasterio; Mustainah; Muhammad Arief; Muh Nawawi (Lembaga Bale Literasi, 2026)
This study aims to analyze the Implementation of the Motor Vehicle Tax Administrative Sanction Elimination Policy in the Perspective of Public Service Transformation in the Banggai Region V Revenue Technical Implementation Unit. The regulation is regulated in the Governor of Central Sulawesi Province Regulation Number 51 of 2022 concerning the procedures for the motor vehicle tax administrative sanction elimination program. The research method is qualitative with a descriptive approach. A total of 9 informants were determined purposively. Data analysis includes data collection, condensation, data presentation, and drawing conclusions. The results of the study indicate that the Motor Vehicle Tax Administrative Sanction Elimination Policy in the Perspective of Public Service Transformation in the Banggai Region V Revenue Technical Implementation Unit according to the Van Meter and Van Horn (1975) implementation model has not been running effectively. Marked by the main problems that lie in the suboptimal achievement of policy goals and objectives, limited socialization related to the elimination program, limited resources and infrastructure, characteristics of implementing organizations that are not yet adaptive, communication between organizations that is not running well, attitudes of implementers that are not fully supportive, and the influence of the social, economic, and political environment that causes the transformation of public services to not be realized optimally.